2021
DOI: 10.15244/pjoes/132621
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Air Pollution: Are Environmental Taxes Enough to Help the EU Member States Reach Climate Neutrality by 2050?

Abstract: Recently, the European Union has officially announced that its' objective in terms of environmental policy is to achieve climate neutrality, including long-term low greenhouse gas emission, by 2050. In light of this, the current study aims to offer a new and updated perspective on the effectiveness of environmental taxes in reducing air pollution in the European Union. Firstly, cluster analysis is used to group the member states of the European Union according to characteristics that will make the research res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Many existing thermal power plants (TPPs) and CHPs throughout Europe have to face their advanced age, deteriorated efficiency and the strengthening pressure to lower their carbon footprint [7,8] both due to legislation [9] and growing carbon price [10,11]. On the contrary to radical solutions such as rapid shut down of coal power plants which is associated with immense costs [12], rehabilitation and repowering of the existing units to prolong their service, increase their efficiency and decrease the pollutants emissions appears more feasible [13,14].…”
Section: Current Situationmentioning
confidence: 99%
See 1 more Smart Citation
“…Many existing thermal power plants (TPPs) and CHPs throughout Europe have to face their advanced age, deteriorated efficiency and the strengthening pressure to lower their carbon footprint [7,8] both due to legislation [9] and growing carbon price [10,11]. On the contrary to radical solutions such as rapid shut down of coal power plants which is associated with immense costs [12], rehabilitation and repowering of the existing units to prolong their service, increase their efficiency and decrease the pollutants emissions appears more feasible [13,14].…”
Section: Current Situationmentioning
confidence: 99%
“…4) is lower. (9) where ṁ 17 is the mass flow of feed water from the degasser, ṁ toHRSG is the part of the feed water pumped to HRSG, and ṁ toHTWH 1…”
Section: Mathematical Modelmentioning
confidence: 99%
“…The findings showed that income from environmental taxes as a percentage of GDP considerably reduced ecological deficits after a certain threshold level, but not cropland balance accounts. Tibulca [6] provided a fresh look at the efficacy of environmental fees in decreasing air pollution in the European Union. Panel data dynamic error correction models were employed in the study to examine the influence of environmental taxes (and other explanatory factors) on carbon dioxide emissions on the one hand, and greenhouse gas emissions in general on the other hand.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This brings to the forefront the debate about how to attain this goal in the most effective way possible. The introduction of environmental fees is a commonly utilized approach for decreasing air pollution [6]. The argument behind environmental taxes is that pollution is a kind of market failure caused by negative externalities associated with certain activities (such as transportation) or the manufacturing process for specific commodities such as energy [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation